A convenient synthesis and crystal structure of disubstituted 1, 2, 3-triazoles having ether functionality. Issue 24 (17th December 2019) - Luxmi, Raj; Kaushik, C. P.; Kumar, Devinder; Kumar, Krishan; Pahwa, Ashima; Sangwan, Jyoti; Chahal, Manisha
Abstract: A series of 27 ether-linked 1, 4-disubstituted 1, 2, 3-triazoles (8a–8z1 ) has been synthesized by 1, 3 dipolar cycloaddition of 1-substituted-4-(prop-2-yn-1-yloxy)benzene (3a–3c ) and aromatic azides (5a–5c, 7a–7f ). The synthesized compounds were explicated by FTIR, 1 H NMR, 13 C NMR and HRMS techniques. The structures of synthesized triazoles 8c (CCDC 1840219) and 8f (CCDC 1840220) were also confirmed by X-ray crystallography. GRAPHICAL ABSTRACT: